Persistence of bipartidism in Valle del Cauca 1992- 1995 - Hau, Alexandra (2016)
This paper analyzes the persistence of bipartidism in Valle del Cauca (Colombia), from the results of the local council elections in the 42 districts of the department, between 1992 and 2015. In order to explain this electoral phenomenon, a classic institutional variable such as the magnitude of the district (MD) is used.Using panel data on a random effects model, this paper seeks to assess the existence of a causal relation between MD and the fragmentation of the party system. Then, it shows in which districts, of specific magnitude, the persistence was stronger. In other words, in which districts the transition process to a multiparty system takes longer and what are the key moments during this process.To analyze the persistence of bipartidism the segmented Nagayama Triangle (Nagayama, 1997; Grofman, Chiaramonte, D’Alimonte & Feld, 2004) is used, which reveals information about the nature of party competition. Results show that in Valle del Cauca the year 2000 represented the key moment in the transition from a two party system to a multiparty one.On synthesis, this paper explains the transition of the numeric format of the party system under a temporal perspective and it shows the difference on the speed of this changes, for districts of different magnitude. The results show that districts of bigger magnitude migrate faster from a two party logic to a format with a larger number of competitors (a multiparty one); in contrast to the districts of smaller magnitude.